Novel simple topology coreless TMR array current sensor. (11th May 2021) - Xu, X P; Liu, T Z; Zhu, M; Wangs, J G
Abstract: Traditional coreless current sensors have multiple magnetic sensors, the same number of operational amplifier and analog-to-digital converter (ADC). This requires more components and basically cannot meet the practical use because of area-effective and cost-effective requirements. In this paper a novel coreless tunnel magnetoresistance (TMR) array current sensor has the characteristics of simple N-1-1 topology, light weight, and low power consumption. Three TMRs are directly connected in parallel and unified only by one programmable amplifier to directly output to meet the current measurement. A relatively simple circuit structure is adopted and a good result is obtained. Finally, the applicability of the scheme is verified by theoretical analysis and actual measurement.